Devices for thoracic endovascular aortic repair of type B aortic dissection: is there any chance for Marfan syndrome?. (2nd July 2020) - Lovato, Luigi; Cefarelli, Mariano; Gatta, Emanuele; Di Eusanio, Marco; Fattori, Rossella
ABSTRACT: Introduction: Type B aortic dissection (TBAD) is a threatening event that may lead to death for aortic rupture or multivisceral malperfusion in the acute phase and offers a poor prognosis for long term survivors. Thoracic endovascular aortic repair (TEVAR) has become the preferential therapy in acute and chronic complicated cases for its less invasivity compared to open surgery. However TEVAR is still encumbered by a significant number of reinterventions, caused by aortic neck aneurysmal degeneration, endoleaks and stent-graft induced new entry (SINE). This is even more true in patients with particularly fragile aortic wall like Marfan Syndrome (MS) in contrast to the excellent results of elective open surgery. Areas covered: This review analyzes the current available TEVAR devices and techniques in TBAD and their technological advancements, especially those most suitable to TBAD anatomy, according to current literature. Expert opinion: The continuous technological evolution of materials and device solutions ensures solid results of TEVAR in acute TBAD and may also potentially overcome some of the limitations of endovascular devices in this setting, paving the way for safer and more durable results and allowing for expanded indications in the future, even in the delicate population of collagenopathies, especially in MS.